2021
DOI: 10.1002/hep.31750
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach Enables Quantitative Measurement of Liver Histology and Disease Monitoring in NASH

Abstract: BaCKgRoUND aND aIMS: Manual histological assessment is currently the accepted standard for diagnosing and monitoring disease progression in NASH, but is limited by variability in interpretation and insensitivity to change. Thus, there is a critical need for improved tools to assess liver pathology in order to risk stratify NASH patients and monitor treatment response. appRoaCH aND ReSUltS: Here, we describe a machine learning (ML)-based approach to liver histology assessment, which accurately characterizes dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 34 publications
2
128
1
Order By: Relevance
“…Application of ML had been explored for pattern recognition in NAFLD using liver biopsy images, 28 ultrasonography, 29,30 and clinical data 31–33 ; however, these are unsatisfactory for the differential diagnosis between NAFLD and NASH and for staging liver fibrosis in NASH 34 …”
Section: Discussionmentioning
confidence: 99%
“…Application of ML had been explored for pattern recognition in NAFLD using liver biopsy images, 28 ultrasonography, 29,30 and clinical data 31–33 ; however, these are unsatisfactory for the differential diagnosis between NAFLD and NASH and for staging liver fibrosis in NASH 34 …”
Section: Discussionmentioning
confidence: 99%
“…A recent paper evaluating a machine-learning (ML) based-approach with paired biopsies from 3 large NASH RCTs including patients with advanced fibrosis (STELLAR-3, STELLAR-4 and ATLAS) 60 showed that these artificial intelligence-driven techniques are sensitive and reliable, and represent promising approaches to correlate dynamic changes in fibrosis (even in the F4 stage) with clinical outcomes, although the number of events in those clinical trials was very small and further studies are required to increase the confidence in this novel and exciting techniques. cluding hepatic collagen and fat content and α-SMA expression.…”
Section: Improved Histological Readingsmentioning
confidence: 99%
“…In an attempt to mitigate the inter and intra‐observer variability in NASH histology readings discussed in the first section, improved machine‐driven methods to quantify basal amount of fibrosis and changes in time are being increasingly explored in the last few years. A recent paper evaluating a machine‐learning (ML) based‐approach with paired biopsies from 3 large NASH RCTs including patients with advanced fibrosis (STELLAR‐3, STELLAR‐4 and ATLAS) 60 showed that these artificial intelligence‐driven techniques are sensitive and reliable, and represent promising approaches to correlate dynamic changes in fibrosis (even in the F4 stage) with clinical outcomes, although the number of events in those clinical trials was very small and further studies are required to increase the confidence in this novel and exciting techniques.…”
Section: Suggested Surrogates and New Biomarkersmentioning
confidence: 99%
“…Algorithms in arti cial intelligence (AI) may resolve issues with interrater variability [54], measurement uncertainty and error by providing quantitative assessments of tissue histology and other tangential tasks which may be of immediate value [55,12,56,57,58,59]. A combination of both rater uncertainty and incomplete information about the histology may present additional challenges for training and evaluating AI technologies.…”
Section: Opportunitiesmentioning
confidence: 99%